(untitled) (Latakia University Journal -Engineering Sciences Series, 2016)
إن عملية المعالجة بالحمأة المنشطة واحدة من عمليات معالجة مياه الصرف الصحي المنزلية والصناعية الأكثر شيوعاً. وتعد فعالية ترسيب الحمأة في المرسبات مقياساً لمدى كفاءة عمل المحطة ككل. وفي هذا البحث تم دراسة العلاقة بين خصائص ترسيب الحمأة وأداء وحدات التهوية في عملية المعالجة بالحمأة المنشطة, وذلك عن طريق إجراء تجارب الترسيب على محطة تجريبية تعمل بنظام الحمأة المنشطة المهواة بمعدل عالي. وكذلك تم إجراء مجموعة من التجارب على مياه محطة معالجة مرج معيربان التي تعمل بالتهوية المديدة لدراسة العوامل المؤثرة في ترسيب الحمأة المنشطة وذلك بالاعتماد على مؤشر حجم الحمأة SVI وسرعة الترسيب الأعظمية UMAX والزمن الموافق لسرعة الترسيب الأعظمية TUMAX. عند المعالجة بنظام الحمأة المنشطة المهواة بمعدل عالي وجد أن بارامترات الترسيب التجريبية (Vo, n) حساسة جداً وتتغير إلى حد كبير بتغير قيم المواد الصلبة المعلقة MLSS في حوض التهوية, وباستخدام العلاقات الرياضية يمكن التنبؤ بقيمة (Vo, n) واستخدامها لتصميم واختيار نظام تشغيل الحمأة دون اللجوء لإجراء اختبارات الترسيب التقليدية. أما عند المعالجة بالتهوية المديدة فوجدنا أن سرعة الترسيب الأعظمية UMAX هي المؤشر الأكثر أهمية في عملية الترسيب ونحصل على معاملات ارتباط (R2) جيدة بين UMAXوكل من(SVI , MLSS, TUMAX) فكانت عند درجة حرارة (20OC) كانت على التوالي (%98,96,98) وعند درجة الحرارة(17OC) على التوالي (%97,96,97) وهي تقريباً نفس القيم. ووجدنا أيضاً أن مؤشر حجم الحمأة SVI يرتبط ارتباطاً وثيقاً ببارامترات الترسيب (TUMAX,UMAX) عند درجة الحرارة(OC20) كانت معاملات الارتباط (%99,98) على التوالي, وعند درجة الحرارة(OC17) بمعاملات ارتباط (%9798,), سرع الترسيب UMAX كانت أكبر وزمن الترسيب TUMAX كان أصغر عند درجة الحرارة (20OC) مما يدل على تحسن الترسيب بارتفاع درجة الحرارة. وكانت النتيجة أن درجة الحرارة عامل مؤثر على الترسيب ومن الضروري أخذها في الحسبان في عمليات تصميم وتشغيل محطات المعالجة بالحمأة المنشطة. The activated sludge is one of the most common methods of sewage treatment , which has been studied through to find the relation between sedimentation properties and the performance of aeration units. sedimentation experiments were applied on a highly- aerated activated sludge experimental treatment plant .Also, another experiments were applied on Marj Maerban treatment plant which is operated using the extended aeration method in order to find the Factors influencing the settling of activated sludge . These experiments were done using the Sludge volume index (SVI) ,the maximum velocity sedimentation rate (UMAX) and the time corresponding to the maximum velocity of sedimentation (TUMAX).In experimental treatment plant. We found that the sedimentation experimental parameters (Vo, n) are very sensitive and can be changed significantly with changing the values of suspended solids (MLSS) in the aeration tank. The mathematical relationships can be used to predict the value of (Vo, n) as well as designing and selecting the operating system of sludge without resorting to a conventional sedimentation tests . We also found in the extended aeration the maximum velocity sedimentation rate (UMAX) is the most important in settling process as we got some good correlation coefficients (R2) between UMAX and (TUMAX, MLSS, SVI) was at a temperature (20OC) were respectively (98, 96,98%), and when the temperature (17 OC) respectively (97,96,97%) which is almost the same values. We noticed that the sludge volume index (SVI) is closely associated with the settling parameters (UMAX, TUMAX) with the correlation coefficients were respectively (98,99%) on the temperature of (20OC) and (98,97%) on the temperature of (17OC) . Velocity sedimentation rate (UMAX) was the largest and deposition time (TUMAX) was smaller on the temperature of (20OC) Indicating an improved sedimentation with higher temperatures . Subsequently, temperature is an influential factor on deposition and It is necessary to be taken into account in the design and operation of activated sludge treatment plan.